STARTER SYSTEM LEARNING MEDIA TO IMPROVE LEARNING OUTCOMES IN VOCATIONAL SCHOOL - Suyitno Suyitno; Yusri bin Kamin; Nurma Amri Lukman; Widiyatmoko Widiyatmoko; Dwi Jatmoko; Aci Primartadi (Universitas Negeri Yogyakarta, 2021)
This study aimed to develop the starter system’s learning media on a motorcycle and analyze the effect on students’ learning outcomes. This developmental research used the 4D model. Experts, teachers, and students were involved in validating the product’s content and feasibility. Quasi-experimental was applied to test the effect of using media on 14 students of the eleventh grade of automotive engineering expertise as an experimental class and 14 students as a control class. The data were collected using questionnaires and tests, then analyzed using an independent t-test. The results show that the learning media for the starter system stand on a motorcycle is feasible for learning. Based on the expert judgment, media have been declared good media, and students showed their interest in using the media. There was a significant difference in students’ learning outcomes that use and without media use.